2018
DOI: 10.5935/abc.20180184
|View full text |Cite
|
Sign up to set email alerts
|

Up to 15-Year Survival of Men and Women after Percutaneous Coronary Intervention Paid by the Brazilian Public Healthcare System in the State of Rio de Janeiro, 1999-2010

Abstract: BackgroundPercutaneous coronary intervention (PCI) is the most frequently used invasive therapy for ischemic heart disease (IHD). Studies able to provide information about PCI's effectiveness should be conducted in a population of real-world patients.Objectives To assess the survival rate of IHD patients treated with PCI in the state of Rio de Janeiro (RJ).MethodsAdministrative (1999-2010) and death (1999-2014) databases of dwellers aged ≥ 20 years old in the state of RJ submitted to one single PCI paid by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
2
5
0
1
Order By: Relevance
“…The factors that determined higher or lower survival in patients with STEMI were consistent with other national 36 and international 26,37,38 studies that showed worse survival in women with conditions such as HF and CKD and in women with a high Killip classification at hospital admission.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The factors that determined higher or lower survival in patients with STEMI were consistent with other national 36 and international 26,37,38 studies that showed worse survival in women with conditions such as HF and CKD and in women with a high Killip classification at hospital admission.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies examining differences in survival between the sexes also showed higher short- and medium-term survival in men than in women. 36,37,39 A study conducted in Rio de Janeiro that examined the survival of 19,263 patients with STEMI indicated that women had worse survival than men when followed up at 30 days and 1 year. However, they had better survival rates at 15 years, particularly in the age group ≥70 years 36.…”
Section: Discussionmentioning
confidence: 99%
“…Nesse estudo, mulheres, em comparação a homens, apresentaram maior taxa de sobrevida em 15 anos após ICP. 113 …”
Section: Mortalidadeunclassified
“…Atrial fibrillation (AF) is the most common sustained arrhythmia, and a significant risk factor for stroke, heart failure and mortality. 25,26 The SAFIRA study, 27 recently published in the RPC journal, aimed to determine the prevalence and epidemiology of AF in a large sample of 7500 elderly Portuguese individuals. The study included a significant subset of 400 individuals that underwent 24-hour Holter monitoring and another subset of 200 individuals which had a 2-week event loop recorder to identify paroxysmal AF.…”
Section: Arrhythmiasmentioning
confidence: 99%